Silver Nanoparticles Synthesized by Using Bacillus cereus SZT1 Ameliorated the Damage of Bacterial Leaf Blight Pathogen in Rice - Ahmed, Temoor; Shahid, Muhammad; Noman, Muhammad; Niazi, Muhammad Bilal Khan; Mahmood, Faisal; Manzoor, Irfan; Zhang, Yang; Li, Bin; Yang, Yong; Yan, Chengqi; Chen, Jianping (Pathogens (Basel), 2020)
Amongst serious biotic factors deteriorating crop yield, the most destructive pathogen of rice is Xanthomonas oryzae pv. oryzae (Xoo), which causes bacterial leaf blight (BLB) disease. This study involved targeted use of biogenic silver nanoparticles (AgNPs) to control BLB in order to cope with the disadvantages of chemical disease control. AgNPs were biologically synthesized from natively isolated Bacillus cereus strain SZT1, which was identified through 16S rRNA gene sequence analysis. Synthesis of AgNPs in bacterial culture supernatant was confirmed through UV-VIS spectroscopy. Fourier transform infrared spectroscopy (FTIR) confirmed that the existence of AgNPs was stabilized with proteins and alcoholic groups. X-ray diffraction (XRD) data revealed the crystalline nature and imaging with scanning electron microscopy (SEM) and transmission electron microscopy (TEM), showing the spherical shape of AgNPs with particle sizes ranging from 18 to 39 nm. The silver presence in AgNPs was further confirmed by energy dispersive spectra. Biogenic AgNPs showed substantial antibacterial activity (24.21 ± 1.01 mm) for Xoo. In a pot experiment, AgNPs were found to be effective weapons for BLB by significantly increasing the plant biomass with a decreased cellular concentration of reactive oxygen species and increased concentration of antioxidant enzyme activity.